Estimating the Gerber-Shiu Expected Discounted Penalty Function for Lévy Risk Model - Yujuan Huang; Wenguang Yu; Yu Pan; Chaoran Cui (Discrete Dynamics in Nature and Society)
This paper studies the statistical estimation of the Gerber-Shiu discounted penalty functions in a general spectrally negative Lévy risk model. Suppose that the claims process and the surplus process can be observed at a sequence of discrete time points. Using the observed data, the Gerber-Shiu functions are estimated by the Laguerre series expansion method. Consistent properties are studied under the large sample setting, and simulation results are also presented when the sample size is finite.